Pembatalan Perkawinan di Pengadilan Agama yang Diajukan Atas Dasar Paksaan Ditinjau Berdasarkan Undang-Undang Perkawinan dan Hukum Islam - Vanisa Vinabilah; Hazar Kusmayanti; Fatmi Utarie Nasution (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Marriage can be canceled if it fails to meet the legal requirements specified in the Marriage Law and the Compilation of Islamic Law, such as when the marriage lacks the consent of both prospective spouses or is coerced, as evidenced in the decisions of the Depok Religious Court Number 3617/Pdt.G/2021/PA.Dpk and the Gorontalo Religious Court Number 0308/Pdt.G/2017/PA.Gtlo. This research aims to examine and analyze the validity of marriage cancellations filed on grounds of coercion under the Marriage Law and Islamic law. The study adopts a normative juridical approach with descriptive-analytical research specifications, using secondary data collected through literature review and field studies involving interviews. The method of data analysis employed is qualitative normative analysis. Based on the research findings, the validity of the cancellation rulings in both cases is confirmed because they fulfill the legal prerequisites for marriage cancellation as outlined in Article 22 and Article 27 paragraph (1) of the Marriage Law, in conjunction with Article 71 letter (f) and Article 72 of the Compilation of Islamic Law.